A brand-new strategy for remarkable improvements of electrochemical performances on conducting polymer-based flexible supercapacitors by coating MoNiP. (20th September 2017) - Zhao, Liping; Yang, Chunming; Shen, Ping; Wang, Zhiyu; Deng, Cuifen; Yang, Lishan; Li, Junhua; Qian, Dong
Graphical abstract: Highlights: We demonstrate a novel strategy to improve the supercapacitive properties of CPs. The supercapacitive properties of CPs can be boosted by electrodeposition of MoNiP. The excellent performances of MoNiP coated CPs stem from its rational structure. Abstract: We demonstrate a novel and universal strategy to significantly boost electrochemical performances of conducting polymer-based flexible supercapacitors via the relatively facile electrodeposition of MoNiP compounds. The fabricated MoNiP@polyaniline (PANI)@carbon fiber cloth (CFC) sandwiched hybrid, for instance, delivers 94.6% of specific capacitance retention from 1 to 40 mA cm −2 and 92.3% of specific capacitance retention at a high current density of 40 mA cm −2 after 2000 cycles, much greater than 56.8% and 58.3% for the uncoated PANI@CFC with MoNiP, respectively. With increasing the numbers for repeatedly alternate coating PANI and MoNiP layer by layer, the specific capacitances rise almost linearly. Simultaneously, the capacitance retentions maintain high levels at 40 mA cm −2 after 2000 cycles. A remarkable decrease in the charge transfer resistance and a markedly enhanced hydrophilicity with coating MoNiP on the surface of PANI@CFC can be found, which can greatly facilitate the electron and electrolyte ion transfer processes and thereby bring with it improved supercapacitive performance. Likewise, the supercapacitive performances of polypyrrole and poly(3, 4-ethylenedioxythiophene) can be significantly enhanced in comparison with their MoNiP uncoated counterparts.